PENERAPAN MODUL BERBASIS PROJECT BASED LEARNING PADA MATA KULIAH ANALISIS REAL 2 - Yurinanda, Sherli; Multahadah, Cut; Z, Gusmanely (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
The education dharma program states that lecturers have the main task of administering education. Permenristekdikti No. 44 of 2015 states the minimum criteria for the learning process, namely CPL (Graduate Learning Outcomes). CPL requires student-centered learning and the role of the lecturer as a facilitator so that Student Center Learning (SCL) is created. Real Analysis 2 which is a follow-up course from Real Analysis 1. Real Analysis 2 is a pure mathematics course that contains a collection of definitions and theorems and lemmas that involve proof. So far, learning real analysis is difficult for students to accept, namely making connections between one rule and another. One learning model that facilitates students to fulfill the CPL for Real Analysis 2 course is the PjBL (Project Based Learning) model. PjBL implementation must be supported by adequate learning facilities. Therefore, a module based on the PjBL model is needed. The use of this PjbL-based module is expected that students will be able to solve mathematical problems and support the fulfillment of CPL courses which results in the formation of creative and systematic mathematics students who are good at solving problems and have the capabilities and competencies needed by the world of work.